2021
DOI: 10.3389/fpls.2021.702874
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Relieves Ozone Stress in Grape Leaves by Inhibiting Ethylene Biosynthesis

Abstract: Ozone (O3) stress severely affects the normal growth of grape (Vitis vinifera L.) leaves. Melatonin (MT) plays a significant role in plant response to various abiotic stresses, but its role in O3 stress and related mechanisms are poorly understood. In order to understand the mechanism of MT in alleviate O3 stress in grape leaves, we perform a transcriptome analyses of grapes leaves under O3 stress with or without MT treatment. Transcriptome analysis showed that the processes of ethylene biosynthesis and signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…In rice, induction of the homologous gene, OsASMT1 , occurred following exposure to the cytokinin benzylaminopurine ( Bhowal et al, 2021 ) which is known to stimulate cell division. In tomato, melatonin enhances the expression of heat shock proteins following heat stress, improving thermotolerance ( Xu et al, 2016 ; Wang et al, 2018 ), while in grape, the role of ASMT1 was related to enhanced ozone tolerance in leaves ( Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In rice, induction of the homologous gene, OsASMT1 , occurred following exposure to the cytokinin benzylaminopurine ( Bhowal et al, 2021 ) which is known to stimulate cell division. In tomato, melatonin enhances the expression of heat shock proteins following heat stress, improving thermotolerance ( Xu et al, 2016 ; Wang et al, 2018 ), while in grape, the role of ASMT1 was related to enhanced ozone tolerance in leaves ( Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MEL treatment resulted in a considerable decrease in H 2 O 2 levels as well as increased antioxidant machinery (Wei et al, 2019). MEL application significantly improved growth status, photosynthesis, antioxidant activity of enzymes, and depletion of ROS generation in ozone-stressed grape leaves (Liu et al, 2021). Jahan et al (2020) observed that MEL application significantly increased micro and macro-nutrient absorption under nickel toxicity in tomato roots and leaves, whereas MEL treatment significantly lowered nickel deposition in both root and shoot system.…”
Section: Melatoninmentioning
confidence: 95%
“…Mt crosstalk with various plant growth regulators helps stress alleviation; for example, grape leaves grown under O 3 were treated with MT modulated ethylene biosynthesis and signalling. O 3 induced a significant increase in genes expression linked with ethylene biosynthesis, while MT supplementation significantly inhibited the ethylene genes expression ( Liu et al, 2021 ). Further MT application also improved the photosynthetic performance and antioxidant activities under O 3 .…”
Section: Melatonin Induce Elevated Ozone Tolerance In Plantsmentioning
confidence: 99%
“…Further MT application also improved the photosynthetic performance and antioxidant activities under O 3 . The over-expression of MT synthesis gene VvASMT1 (acetylserotonin methyltransferase 1) also alleviated the O 3 stress and reduced the ethylene biosynthesis ( Liu et al, 2021 ). The effect of diverse MT concentrations (0, 0.1, 0.5, 2.5, and 12.5 μM) was studied on apple plants grown under O3 stress.…”
Section: Melatonin Induce Elevated Ozone Tolerance In Plantsmentioning
confidence: 99%